Long-term reactive nitrogen loading alters soil carbon and microbial community properties in a subalpine forest ecosystem. (January 2016) - Boot, Claudia M.; Hall, Ed K.; Denef, Karolien; Baron, Jill S.
Abstract: Elevated nitrogen (N) deposition due to increased fossil fuel combustion and agricultural practices has altered global carbon (C) cycling. Additions of reactive N to N-limited environments are typically accompanied by increases in plant biomass. Soil C dynamics, however, have shown a range of different responses to the addition of reactive N that seem to be ecosystem dependent. We evaluated the effect of N amendments on biogeochemical characteristics and microbial responses of subalpine forest organic soils in order to develop a mechanistic understanding of how soils are affected by N amendments in subalpine ecosystems. We measured a suite of responses across three years (2011–2013) during two seasons (spring and fall). Following 17 years of N amendments, fertilized soils were more acidic (control mean 5.09, fertilized mean 4.68), and had lower %C (control mean 33.7% C, fertilized mean 29.8% C) and microbial biomass C by 22% relative to control plots. Shifts in biogeochemical properties in fertilized plots were associated with an altered microbial community driven by reduced arbuscular mycorrhizal (control mean 3.2 mol%, fertilized mean 2.5 mol%) and saprotrophic fungal groups (control mean 17.0 mol%, fertilized mean 15.2 mol%), as well as a decrease in N degrading microbial enzyme activity. Our results suggest that decreases in soil C in subalpine forests were in part driven by increased microbial degradation of soil organic matter and reduced inputs to soil organic matter in the form of microbial biomass. Highlights: N amendments decreased organic soil pH, microbial biomass C and % C. N amendments altered microbial community structure. Fertilization decreased arbuscular mycorrhizal and saprotrophic fungal abundance. Spring, but not fall bacterial abundance was reduced by N amendments. N degrading enzymes activities were elevated in N amendment plots.